Thrombomodulin and thrombopoietin, two biomarkers of hemostasis, are positively associated with adherence to the World Cancer Research Fund/American Institute for Cancer Research Recommendations for Cancer Prevention in a population-based cross-sectional study - Grafetstätter, Mirja; Pletsch-Borba, Laura; Johnson, Theron S.; Katzke, Verena; Hoffmeister, Michael; Bugert, Peter; Kaaks, Rudolf; Kühn, Tilman (Nutrients, 2019)
A pro-coagulative state is related to increased risk of cardiovascular diseases but also certain cancers. Since experimental and smaller human studies suggest that diet, physical activity, and body weight may all affect coagulation, we evaluated associations between these lifestyle factors and hemostatic biomarkers in a population-based study. Cross-sectional baseline data from 2267 randomly selected participants of EPIC-Heidelberg (age range 35–65 years) was used. Fibrinogen, glycoprotein IIb/IIIa, P-selectin, thrombomodulin (TM), and thrombopoietin (TPO) were measured in baseline plasma samples. A score reflecting adherence to the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) recommendations for cancer prevention was created. Associations between the WCRF/AICR score as well as its individual components and hemostatic biomarkers were analyzed by linear regression models. Multivariable-adjusted geometric means (95% confidence intervals) of TM and TPO were higher with greater adherence to the WCRF/AICR recommendations (TM, lowest vs. highest score category: 2.90 (2.7,3.1) vs. 3.10 (2.9,3.3) ng/mL, plinear trend = 0.0001; TPO: 328 (302,356) vs. 348 (321,378) pg/mL, plinear trend = 0.0007). These associations were driven by lower alcohol and meat consumption among persons with higher WCRF/AICR scores. Our results indicate that lifestyle factors favorably affect TM and TPO, two hemostatic factors implicated in chronic disease development.
Gesehen am 31.10.2019